Designing and managing multiple pipelines - Aitken, James; Childerhouse, Paul; Christopher, Martin; Towill, Denis R. (Council of Logisticts Management, 2005)
There is now a growing recognition that supply chains should be designed from ‘the customer backwards’ rather than from ‘the company outwards’. If such a view is accepted then the implication is that since the organisation will likely be serving multiple markets or segments there will be the need to design and manage multiple ‘pipelines’ to serve those different customers. To assist decision makers in their choice of appropriate supply chain design a framework is proposed based upon multiple criteria. A case study is presented which highlights the benefits of selecting, engineering and operating multiple pipelines tailored to the needs of the